EXPLORATION OF FOODSTAGRAMMING CONTENT PREFERENCES IN MILLINEAL AND Z GENERATIONS IN WEST SUMATRA - Chandra Syahputra; Sari Lenggogeni; Verinita Verinita; Harry Wahyudi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The goal of this study is to determine the behavior of tourists who use Instagram to discover about local destinations and cuisine in West Sumatra. Instagram, which is the most popular social media among millennials and Generation Z, offers advantages that other social media platforms lack, such as more complex visuals that shape the image and aid individuals interested in gastronomy tourism in West Sumatra Province. The method used in this study is a quantitative survey. This research used a cross-sectional study design, in which data is collected at the same time or period for both independent and dependent variables. The focus of this research is on millennials born between the 1980s and the 1990s. Respondents that use the Instagram social media platform and live outside of West Sumatra province will be sampled for the study. When the visual complexity of the destination image has a CR value of 7.291 (p0.00 ≤ 0,05) and an estimated value of 0.654, Ho is rejected and Ha is accepted, revealing that visual complexity has a positive influence on the destination image. It is well known that the influence of visual complexity on destination image has a CR value of 3.508 (p0.00 ≤ 0,05) with an estimated value of 0.418, showing that Ho is rejected and Ha is accepted, confirming that visual complexity has a positive influence on destination choice. The statistical test findings for hypothesis 3 revealed an estimated parameter value of 0.233, a standard error of 0.114, and a critical ratio value of 1.956 with a probability value of 0.05. With a significance level (alpha) of 0.05, it is possible to conclude that there is insufficient empirically strong evidence to reject Ho, hence Ha is rejected. Therefore, visual complexity increases the image of culinary attractions in West Sumatra. Visual complexity has a significant positive effect on the image of the destination as well as the tourist's destination choice in West Sumatra. Instagram can assist tourists who are considering West Sumatra as a destination for gastrotourism. Keywords: Visual Complexity, Destination Image, Destination Choice, Content Preferences